Biogenic calcium carbonate derived from waste shells for advanced material applications: A review - Azarian, Mohammad Hossein; Sutapun, Wimonlak (Frontiers in Materials, 2022)
Biogenic calcium carbonate derived from waste shells has received significant attention in the last two decades as a replacement for limestone due to its contribution to reducing environmental impact by turning wastes into value-added biomaterial and moving global society toward net-zero waste. Recently, several review papers have been published regarding applying biogenic derived calcium carbonate in engineering, biomedical, electrochemical, and environmental technologies. This review stands apart from other reviews on this topic in terms of focusing and reviewing the published papers used and reported indirect methods only to obtain calcium carbonate from biogenic waste shells and not by direct methods. The direct or untreated methods include simple grinding, ball milling, or mortar and pestle techniques. In contrast, the indirect methods covered in this review paper consist of precipitation and different chemical treatment techniques. Therefore, this review paper aims to comprehensively summarize the usage of calcium carbonate derived from eggshells and seashells by indirect methods and glance at its recent development for advanced material applications including water treatment, bio-filler, and reinforcement in polymer composites, energy application, pharmaceutical, biomedical, and drug delivery applications.